1997
DOI: 10.4098/at.arch.97-32
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical aspects of the energetic effectivenes of huddling in small mammals

Abstract: Canals M., Rosenmann M. and Bozinovic F. 1997. Geometrical aspects o f the energetic effectiveness of huddling in small mammals. Acta Theriologica 42: 321-328.Reduced energy expenditure resulting from huddling in small mammals is mainly attributed to the reduced surface area/volume ratio of the huddling group. Here we propose a model to account for the reduction of the relative exposed area of grouped animals and for the diminution of metabolic rate during huddling. We attempt to explain mechanistically how ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 16 publications
2
62
0
Order By: Relevance
“…From the total of the fitted models, including our results and data from the literature, only in four cases R 2 was lower than 66.67% (see Tables). Previous studies reported a percentage of observed energy saving attributed to the reduced surface effect ranged from 58 to 94% (Canals et al 1997). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…From the total of the fitted models, including our results and data from the literature, only in four cases R 2 was lower than 66.67% (see Tables). Previous studies reported a percentage of observed energy saving attributed to the reduced surface effect ranged from 58 to 94% (Canals et al 1997). …”
Section: Discussionmentioning
confidence: 97%
“…This parameter was called deformation coefficient because it represents twice the average surface lost by the huddled individuals and determines the effectiveness of animals in reducing the metabolic rate of the group from huddling (HE -huddling effectiveness) (Canals et al 1997). The f(rc) parameter is affected by the number of grouped individuals (n) and by the temperature gradient between body (Tb) and ambient (T a ), that is (Tb -T a ).…”
Section: Introductionmentioning
confidence: 99%
“…Each individual in the model enters winter with a unique body and fat mass and arouses with a unique pattern throughout winter. All individuals in a population are subjected to the same winter length, number and pattern of disturbances (see below), and each population either clusters in groups of greater than 5 individuals (Canals et al 1997) or does not cluster.…”
Section: Methodsmentioning
confidence: 99%
“…Most cavernicolous species cluster to some extent, and even small clusters (5 individuals) significantly reduce heat loss by individuals (Canals et al 1997;Kurta 1985). To estimate the energetic benefit of clustering, we ran all simulations with and without clustering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation